Synthesis and Crystal Structure of 1-(4-Nitrobenzyl)-3-allyl-1H-benzo[d]imidazol-2(3H)-one - Dounia Belaziz; Santiago V. Luis; Youssef Kandri Rodi; Inés Martí; Vicente Martí-Centelles (Journal of Chemistry)
A functionalized benzimidazole, 1-(4-nitrobenzyl)-3-allyl-1H-benzo[d]imidazol-2(3H)-one, has been synthesized, and the crystal structure was determined and analyzed. This compound crystallizes in the monoclinic, space group P21/n (number 14) c with cell parameters, a=7.12148(8) Å, b=16.12035(17) Å, c=13.04169(17) Å, β=93.3043(11), V=1494.71(3) Å3, and Dcalc = 1.375 g/mm3. The solid state geometry is stabilized by intermolecular π–π interactions along with the van der Waals interactions which contribute to the stability of the crystal packing. Computational calculations have been used to properly understand the main intermolecular interactions present in the crystal.